1986
DOI: 10.1021/bi00358a027
|View full text |Cite
|
Sign up to set email alerts
|

Ionization state of the coenzyme 5'-phosphate ester in cytosolic aspartate aminotransferase. A Fourier transform infrared spectroscopic study

Abstract: In order to determine the ionization state of the 5'-phosphate of bound pyridoxal phosphate, a Fourier transform infrared spectroscopic study of cytosolic aspartate aminotransferase has been carried out. Dianionic and monoanionic phosphate monoesters give rise to two bands each in the infrared spectrum [Shimanouchi, T., Tsuboi, M., & Kyogoku, Y. (1964) Adv. Chem. Phys. 8, 435-498]. These bands can be identified in infrared spectra of the free coenzyme in solution. Due to interfering bands arising from the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The interaction of unlabeled ShB and ShB-L7E peptides with the anionic PA vesicles can also be assessed by monitoring the infrared absorbance bands at 1180 and 980 cm-1 arising from different stretching vibrations of the monoanionic and dianionic forms, respectively, of the PA phosphoryl group (Sanchez-Ruiz and Martinez-Carrion, 1986;Bhushan and McNamee, 1993). Monitoring of the pH dependence of the above infrared bands in plain PA vesicles, exactly as described by Bhushan and McNamee (1993), makes it possible to calculate a pKa of -8.0 corresponding to the deprotonation of the monoanionic phosphoryl group to produce the dianionic form (data not shown).…”
Section: Binding Of Peptides To Phospholipid Vesiclesmentioning
confidence: 99%
“…The interaction of unlabeled ShB and ShB-L7E peptides with the anionic PA vesicles can also be assessed by monitoring the infrared absorbance bands at 1180 and 980 cm-1 arising from different stretching vibrations of the monoanionic and dianionic forms, respectively, of the PA phosphoryl group (Sanchez-Ruiz and Martinez-Carrion, 1986;Bhushan and McNamee, 1993). Monitoring of the pH dependence of the above infrared bands in plain PA vesicles, exactly as described by Bhushan and McNamee (1993), makes it possible to calculate a pKa of -8.0 corresponding to the deprotonation of the monoanionic phosphoryl group to produce the dianionic form (data not shown).…”
Section: Binding Of Peptides To Phospholipid Vesiclesmentioning
confidence: 99%
“…W have recently shown that Fourier-transform infrared (FTIR)1 spectroscopy can be a valuable technique to determine the ionization state of protein-bound phosphoryl groups for coenzyme-dependent enzymes (Sanchez-Ruiz & Martinez-Carrion, 1986).…”
mentioning
confidence: 99%
“…Pyridoxal phosphate-containing enzymes play an important role in the biological processes where they act as coenzymes catalyzing different reactions involved in the metabolism of amino acids. The biological potentialities of pyridoxal phosphate enzymes are determined, to a great extent, by the presence of an aldehyde and phenolic hydroxyl groups as well as pyridine nitrogen atom [1][2][3][4][5][6][7][8][9][10][11][12]. The aldehyde group is needed to form an external Schiff base with the substrate.…”
Section: Introductionmentioning
confidence: 99%